Marc de Vos: European Flexicurity and Globalization: A Critical Perspective: The International Journal of Comparative Labour Law and Industrial Relations 25, no. 3. (2009); 209 – 235 - Kiss, György (Pécsi Munkajogi Közlemények, 2026)